Pengaruh Strategi Content Marketing Instagram Terhadap Point Of Purchase Kruv Studio - Talita Karisma Syaharani; Nurul Azizah (Journal of Management and Social Sciences, 2024)
In this digital era, the role of marketing strategy is crucial to the success of a business. With widespread technological advances, companies are not only faced with demands to innovate but also to deeply understand the behavior of consumers who are increasingly connected and intelligent. This research aims to explore and analyze the influence of content marketing strategies on Point Of Purchase at KruV Studio. To understand how content marketing strategies can be key in shaping perceptions and increasing customer enthusiasm. In this research I will focus on the marketing aspects of the Content Marketing strategy on Point Of Purchase at KruV Studio.